Pengaruh Pelatihan, Kompensasi dan Motivasi Terhadap Prestasi Kerja Karyawan di PT Panin Dubai Syariah Bank Kantor Cabang Bandung - Dadang Dimyati (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2021)
Good employee performance can be achieved if every element in the organization is well integrated and able to carry out its role. This research is motivated by the fluctuating work performance of employees. This study aims to determine how the effect of training, compensation and motivation on employee performance at PT Panin Dubai Syariah Bank. The object of this research is the training, compensation, motivation and work performance of the employees of PT Panin Dubai Syariah Bank Bandung Branch Office. The type of research is quantitative associative. The type of data used is primary data and uses data collection techniques through questionnaires and complementary data through observations, interviews, and literature studies. The sampling technique in this study used saturated sampling where the entire population was used as a sample with a total of 30 people. The results showed that there was an effect of training on employee performance, where t count > t table value (22,910> 1,703). Compensation where t count > t table value (10,679>1,703.) Motivation where t count > t table value (5,003>1,703). significant effect on employee performance where tcount > t table value. Simultaneously training, compensation and motivation have a significant effect on employee performance where F count = 167,570 > F table = 4.23